Industry Trends in India’s Automotive Sector : A Study of Electric Vehicles, Market Dynamics, and Financing Patterns. (International Journal of Food and Nutritional Sciences, 2023)
The Indian automotive sector is experiencing rapid transformation, primarily due to the increasing prominence of electric vehicles (EVs). This shift is driven by global sustainability goals, technological advancements, and proactive government policies. This study explores the emerging trends in the Indian EV market from 2020 to 2023, emphasizing consumer preferences, financial challenges, and policy support. Using secondary data from government sources, industry reports, and peer-reviewed journals, the paper identifies major drivers, obstacles, and the role of financing mechanisms. The findings are useful for stakeholders such as policymakers, manufacturers, and financial institutions to understand the direction of the industry and devise future strategies.